Concurrent circulation of dengue serotype 1, 2 and 3 among acute febrile patients in Cameroon. - Huguette Simo Tchetgna; Francine Sado Yousseu; Basile Kamgang; Armel Tedjou; Philip J McCall; Charles S Wondji (PLoS Neglected Tropical Diseases, 2021)
Acute febrile patients presenting at hospitals in Douala, Cameroon between July and December 2020, were screened for dengue infections using real time RT-PCR on fragments of the 5' and 3' UTR genomic regions. In total, 12.8% (41/320) of cases examined were positive for dengue. Dengue virus 3 (DENV-3) was the most common serotype found (68.3%), followed by DENV-2 (19.5%) and DENV-1 (4.9%). Co-infections of DENV-3 and DENV-2 were found in 3 cases. Jaundice and headache were the most frequent clinical signs associated with infection and 56% (23/41) of the cases were co-infections with malaria. Phylogenetic analysis of the envelope gene identified DENV-1 as belonging to genotype V, DENV-2 to genotype II and DENV-3 to genotype III. The simultaneous occurrence of three serotypes in Douala reveals dengue as a serious public health threat for Cameroon and highlights the need for further epidemiological studies in the major cities of this region.